2015
DOI: 10.1093/pubmed/fdu105
|View full text |Cite
|
Sign up to set email alerts
|

Poorer mental health in UK bisexual women than lesbians: evidence from the UK 2007 Stonewall Women's Health Survey

Abstract: More bisexual women reported poor mental health or psychological distress than did lesbians. Bisexual women may be more likely to experience social stress due to the 'double discrimination' of homophobia and biphobia. This stress, experienced mainly as internalized and felt stigma, could result in greater risk for poor mental health compared with lesbians. Addressing both biphobia and homophobia within UK society has important preventative mental health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 54 publications
6
49
0
13
Order By: Relevance
“…3,4 More limited evidence suggests that these disparities also extend to people of other sexual identities who report sexual attraction to or behaviour with both men and women. For example, studies have found elevated levels of outcomes such as psychological distress among "mostly heterosexual" individuals.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 More limited evidence suggests that these disparities also extend to people of other sexual identities who report sexual attraction to or behaviour with both men and women. For example, studies have found elevated levels of outcomes such as psychological distress among "mostly heterosexual" individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence that midlife and young bisexual (and transgender) people have worse mental health outcomes than lesbian and gay people is building (Colledge et al, 2015;Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002) but is little studied in relation to older people. One common explanation for these worse outcomes is minority stress -long term chronic stress stemming from experiences of stigma, marginalisation or discrimination, and functioning as a social determinant of health Meyer, 2003).…”
Section: Lifelong Experiences Of Biphobia May Affect Health and Wellbmentioning
confidence: 99%
“…There is a small speculative literature on the issues older bisexually-identified people are likely to face when encountering support services (Dworkin, 2006;Rodriguez Rust, 2012;Scherrer, 2017) and some evidence that bisexually-identified women are at increased risk of negative health outcomes across the life course compared to lesbians (Colledge, Hickson, Reid, & Weatherburn, 2015;Fredriksen-Goldsen, Kim, Barkan, Balsam, & Mincer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been replicated across many different countries and contexts, as readers of this journal are well aware (e.g., Colledge, Hickson, Reid, & Weatherburn, 2015;Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002;King & McKeown, 2003;Schrimshaw, Siegel, Downing, & Parsons, 2013). Therefore, in presenting a keynote talk (see acknowledgments) on bisexuality it seemed appropriate-even essential-to focus on issues of mental health.…”
Section: Introductionmentioning
confidence: 77%